2016
DOI: 10.1515/scjme-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Internal Combustion Engine Powered by Synthesis Gas from Pyrolysed Plastics

Abstract: The article discusses the application of synthesis gas from pyrolysis of plastics in petrol engine. The appropriate experimental measurements were performed on a combustion engine LGW 702 designated for micro-cogeneration unit. The power parameters, economic parameters in term of brake specific fuel consumption, and internal parameters of the engine were compared to the engine running on the reference fuel - natural gas and synthesis gas. Burning synthesis gas leads to decreased performance by about 5% and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…However, the steam turbine involves the generally in used to (industrial)-(industrial). used as the soot can dam [5,6].…”
Section: Generation Of Electrical Powermentioning
confidence: 99%
“…However, the steam turbine involves the generally in used to (industrial)-(industrial). used as the soot can dam [5,6].…”
Section: Generation Of Electrical Powermentioning
confidence: 99%
“…Chríbik Andrej used synthesis gas produced from pyrolysis of plastics, in petrol engine and they suggested that the synthesis gas has similar properties as natural gas, in terms of burning. They reported that burning synthesis gas leads to decreased performance by about 5% and to increased mass hourly consumption by 120 % [17]. Few researchers reported that the fluids injection has a crucial influence on the internal flows [18].…”
Section: Fig 1 Honge Treementioning
confidence: 99%
“…Most of the research work has been done by mixing oil developed from waste plastic disposal with heavy oil for marine application. The results showed that waste plastic pyrolysis oil when mixed with heavy oils reduces the viscosity comparatively and improves the engine performance [1,6,9]. …”
Section: Plastic Oilmentioning
confidence: 99%